The Influence of Literacy Culture on the Learning Motivation of Fourth Grade Elementary School Students - Suryani, Nurrahmah; Dafit, Febrina (The Future of Education Journal, 2025)
The purpose of this study is to identify the influence of literacy culture on the learning motivation of fourth-grade students at SDN 015 Banjar XII, Rokan Hilir Regency. This research is a quantitative study using an ex post facto design. The population in this study consisted of all fourth-grade students at SDN 015 Banjar XII, totaling 54 students. Sampling in this study was carried out using a census/total sampling technique, so the sample consisted of all 54 fourth-grade students at SDN 015 Banjar XII. The techniques and instruments used for data collection in this study were literacy culture and learning motivation questionnaires. The hypothesis test used in this research was a simple linear regression analysis, which aimed to show the relationship between literacy culture (X) and students' learning motivation (Y). Based on the results of the study, it can be concluded that literacy culture has a positive and significant influence on students' learning motivation. This is supported by the results of the simple linear regression analysis test, which showed a significance value (sig) of 0.000, which is smaller than the probability value of 0.05. Therefore, it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning that there is an influence of literacy culture (X) on students' learning motivation (Y).